2019
DOI: 10.1111/crj.13110
|View full text |Cite
|
Sign up to set email alerts
|

1% Tetracaine hydrochloride injection pure solution aerosol inhalation combined with oral administration of dyclonine hydrochloride mucilage as upper airway anesthesia for bronchoscopy: A randomized controlled trial

Abstract: Background: During the bronchoscopy process, successful passage of the tracheoscope through the glottis can affect the following procedure of bronchoscopy. Therefore, safer, more effective and less painful anesthesia methods are particularly important for the bronchoscopy success rate. Objective: This study aimed to evaluate the efficacy of 1% tetracaine hydrochloride injection pure solution aerosol inhalation combined with oral administration of dyclonine hydrochloride mucilage during bronchoscopy. Methods: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Dyclonine hydrochloride mucilage can reduce throat spasm, eliminate mucus bubbles in the oropharyngeal cavity, and produce a defoaming effect in the gastric cavity, thereby improving the field of vision during electronic gastroscopy [ 6 ]. Further, numerous studies have confirmed better efficacy and safety compared to lidocaine and tetracaine for gastrointestinal endoscopy and tracheal intubation [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dyclonine hydrochloride mucilage can reduce throat spasm, eliminate mucus bubbles in the oropharyngeal cavity, and produce a defoaming effect in the gastric cavity, thereby improving the field of vision during electronic gastroscopy [ 6 ]. Further, numerous studies have confirmed better efficacy and safety compared to lidocaine and tetracaine for gastrointestinal endoscopy and tracheal intubation [ 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Advising patients to use a precontained dacronine gelatin paste and administering intravenous remimazolam and a 5 mL topical spray of 2% lidocaine in the oropharynx prior to induction resulted in smoother hemodynamics during induction. [ 1 ] In this case, we chose remimazolam sedation with mild respiratory inhibition. We used full epineural anesthesia to enhance the patient’s tolerance to LMA placement, reduced the dosage of remimazolam, and avoided excessively deep anesthesia to prevent aggravating the inhibition of voluntary respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that combining pharyngeal surface anesthesia with remimazolam sedation results in smoother hemodynamics during induction. [ 1 ] In this case, we propose a new approach to general anesthesia using a laryngeal mask with preservation of spontaneous respiration, pharyngeal mucosal surface anesthesia, and thoracic paravertebral nerve block (TPVB) combined with remimazolam sedation. This approach aims to provide precise analgesia, moderate sedation, and successful LMA general anesthesia to preserve spontaneous respiration in patients undergoing thoracoscopic pulmonary wedge resection.…”
Section: Introductionmentioning
confidence: 99%